AB0379 Long-term renal outcome after remission induction with cyclophosphamide pulse therapy in patients with lupus nephritis – a single centre experience. (23rd January 2014) - Oelzner, P.; Lungwitz, M.; Busch, M.; Eidner, T.; Wolf, G.
Abstract : Background: Cyclophosphamide (Cyc) pulse therapy is the treatment of choice in patients with proliferative lupus nephritis (LN). Dependent on its definition, a remission of LN is achieved in 54 – 90 % of the patients within 2 – 4 years. However data on long-term outcome and predictors of sustained remission are limited. Objectives: To investigate long-term outcome of LN in patients after remission induction with Cyc pulse therapy including predictors of sustained remission. Methods: SLEDAI, parameters of renal function, presence of active urinary sediment, proteinuria (24 h) and parameters of immunological activity of 58 patients (47 women and 11 men, age at the time of initiation of Cyc pulse therapy 37.5 ± 14.8 years, observation period 75 ± 46 months) with LN (biopsy-proven in 51 patients: WHO class II 27 %, class III 24 %, class IV 31 %, class V 18 %) were collected on 3 time points of the disease course (prior to remission induction with Cyc pulse, after 6 pulses Cyc and at the last documented visit in our department). 44 patients were treated with high dose Cyc (0.75 – 1.0 g/m 2 ) every 4 weeks for at least 6 months, 12 patients received low dose Cyc pulse according to the Euro-Lupus Nephritis Trial (6 pulses 500 mg Cyc every 2 weeks within 3 months) and 2 patients received a combined therapy regime. As primary maintenance therapy 35 patients received azathioprine and 18 mycophenolate mofetil. Complete renal remission (CR) was defined as stable renal function, inactive urinary sediment and a proteinuria of ≤ 0.2 g/day, partial remission (PR) as stable renal function, inactive urinary sediment and a proteinuria of ≤ 0.5 g/day (2). Results: At the end of the observation period 45 % of the patients were in CR, 24 % in PR, 16 % had a persistent significant proteinuria of > 0.5 g/d (mean 1.18 g/day) but stable renal function and inactive sediment and 3 % had a persistent significant renal failure but inactive disease. In 12 % a persistent active renal disease without fulfilling criteria of CR and PR or a renal flare was observed. Doubling in serum creatinine was oberserved only in 1 patient. CR at the end of the observation period was observed in 50 % of patients with low dose and in 43 % of those with high dose Cyc (n.s.). Longterm renal outcome was not dependent from initial maintenance therapy and age of the patients. 4 patients (6.8 %) died during the observation period (2 due to severe infections, 1 due to malignancy and 1 by sudden cardiac death). Patients with CR showed a highly significantly lower proteinuria after 6 pulses Cyc (0.36 ± 0.36 vs. 1.97 ± 1.57 g/d; p=0.000), significantly lower dsDNA-Ab (61 ±72 vs. 110 ± 89 U/ml; p<0.05) at the time point of initiation of maintenance therapy and a significantly lower tubulointerstitial chronicity index in renal biopsy at baseline (0.37 ± 0.40 vs. 1.47 ± 1.13; p=0.001). A proteinuria of < 0.35 g/day after 6 pulses Cyc showed a sensitivity of 71 % and a specificity of 94 % for CR at the end of the observation period. Male gender was associated with no remission (p=0.009). Conclusions: A proteinuria of < 0.35 g/d after 6 pulses Cyc for remission induction is predictive for long-term complete remission of LN. References: Gordon C, Jayne D, Pusey C et al. European consensus statement on the terminology used in the management of lupus glomerulonephritis. Lupus 2009; 18: 257-263 Disclosure of Interest: None Declared